Diversificação de tarefas como proposta metodológica no ensino dos números inteiros - Danczuk, Fabulo Eugenio (2016)
This piece of work has as its main goal to present a Methodological Proposal based on the theory of Ponte (2005, 2006, and 2014) about Diversification of Tasks, in order that this put the students in Activity and make the process of learning possible and meaningful of the formal concepts of Integer, on the historical concept and the four operations. In order to accomplish our Proposal, we sought references on the researches that deal with Records of Semiotic Representations, of Duval (1993, 2003) and on the theories about Games in Math. This way, our Proposal was planned and built based on the movement of action-reflection-action, being applied in a regular classroom of the 7th year (6th grade) of the Middle School, in which the researcher is the Math teacher. This research-action is mostly qualitative, seeking to evaluate if the changes accomplished on the methodology will cause positive impact on the teacher’s role. Later on, based on the collected data through the applied Tasks, according to the theory of Bardin (1977), about Content Analysis. The results point to a real need of the diversification of Tasks on the methodological planning of any teacher that seeks the appropriation of knowledge for their students.